Toxicity assessment of electronic cigarettes. (7th June 2019) - Wang, Guanghe; Liu, Wenjing; Song, Weimin
Abstract: Sale of electronic cigarette (e-cigarette) products has exponentially increased in the past decade, which raise concerns about its safety. This updated review provides the available toxicology profile of e-cigarettes, summarizing evidence from in vitro and in vivo studies. Data regarding which components in e-liquids exhibit potential toxicities are inconsistent. Some studies have reported that nicotine plays a significant role in inducing adverse outcomes and that solvents alone do not induce any adverse effects. However, other studies have suggested that nicotine is not associated with any adverse outcomes, whereas solvents and flavorings are the key components to elicit considerable deleterious effects on cells or animals. In addition, most of the studies that have compared the toxicity of e-cigarettes with tobacco cigarettes have suggested that e-cigarettes are less toxic than tobacco cigarettes. Nevertheless, scientific evidence regarding the toxicity profile of e-cigarette is insufficient owing to the lack of a standardized research approach. In the future, scientific toxicology data derived from standardized testing protocols including nicotine, ingredients analysis, the various e-cigarette devices made from different materials are urgently needed for thorough toxicology assessment. This review aims to update the toxicity profiles, identify knowledge gaps, and outline future directions for e-cigarettes research, which would greatly benefit public health professionals.